Confrontation, strategy and war termination Britain's conflict with Indonesia - Tuck, Christopher (Military strategy and operational art, 2013)
At the heart of this book is the problem of war termination. The British experience in Indonesia in the 1960s represents an illuminating case study of the difficulties associated with strategy and the successful termination of conflicts. The value of this book lies in two areas.